Lack of effect of topical indomethacin on psoriasis. - Green, C A (1987)
Topical 1% indomethacin had no effect on chronic stable plaque psoriasis in an open controlled study using subjective clinical scores nor in a randomised double-blind inert base controlled study using both subjective and objective measurements of lesional response; nor did it initiate or affect the development of psoriasis after cold injury. Previous studies are reviewed and it is concluded that the evidence does not support the hypothesis which relates psoriasis to eicosanoids produced by lipoxygenase activity.